SEASONAL VARIATION OF HEAVY METALS CONCENTRATIONS IN FISH IN OGUTA LAKE, NIGERIA - Nwoko, C.I.A; Ukiwe, L.N.; Egereonu, U. U (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Concentrations of heavy metals iron (Fe), copper (Cu), lead (Pb), nickel (Ni), mercury (Hg), chromium (Cr), cadmium (Cd) and arsenic (As), were determined in the head of four fish species, namely, Trachinotus goreensis, Clarias anguillaris, Synodontis membranaceous, and Tilapia zilli, in Oguta Lake, Nigeria. Result obtained from analyses using Atomic Absorption Spectrophotometry (AAS) revealed that Fe (13.309 mg/l) was the highest metal accumulated by the fish (S. membranaceous) in October, while Hg and As were not detected in all the fish species except in July where 0.003 and 0.005mg/l of As were detected in the fish species (T. zilli and C. anguillaris), and November where 0.001 mg/l of As was also detected in S. membranaceous. The distribution of HMs in the fish species revealed that, overall, Fe was the highest metal accumulated by the fish species, C. membranaceous, followed by T. goreensis. This high level of Fe accumulated by the fish species may be attributed to the fact that Fe occur at high levels in organic matter at the bottom of the Lake. So being typical bottom dwellers, the fish species were more exposed to the metal. Heavy metals were higher (not significantly) during the dry season than the rainy season. Statistically, however, seasonal variation didn’t significantly influence the accumulation of HMs by the fish species. The levels of heavy metals examined in the present study were below maximum permissible limits set by World Health Organization (WHO), indicating that the Oguta Lake is not polluted by heavy metals.